PERANSERTA WANITA PETERNAK SAPI PERAH DALAM MENINGKATKAN TARAF HIDUP KELUARGA - Marsudi Lestariningsih; Basuki Basuki; Endang Endang (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
This research was conducted in a cooperation namely KOPSAE, located in three villages, Jurang Jero, Pujon Lor, and Sebaluh, distric of Pujon. Malang, East Java. The research objective is to investigate the women involvement in improving family life of diery farmer in tose villages and to evaluate the women’s contribution in their family’s revenue. This research results can be used by East Java Animal Husbandary Office, financial institutions, cooperative enterprises, and other external parties in determining prolicies for supervision and improvement of farm business in rural areas. Data are collected through survey. Population used are 40 families who own cows.The result shows that women have potential roles in improving the family’s revenues. The women contribution is approximately 44,99% of total family’s revenues. The women allocate their time about 1-2 hours a day in diery family activities, meanwhile, men spent about 2-4 hours a day. It appears that supervision is still needed for using their idle time in order to improve their skills as well as their revenues.